On the synonymy between Paraponychus corderoi (Baker & Pritchard, 1962) and P. incanus Gonzalez & Flechtmann, 1977 (Acari, Tetranychidae) - Hernandes, Fabio Akashi [UNESP]; Feres, Reinaldo J. F.; Flechtmann, Holger Wenzel Flechtmann (Systematic & Applied Acarology Soc London, Natural History Museum, 2011)
In this paper we propose a new synonymy between P. corderoi (Baker & Pritchard, 1962) and P. incanus Gonzalez & Flechtmann, 1977, based on the examination of type-specimens.